Investigating a Simple and Sensitive High-performance Liquid Chromatography Method for Simultaneous Determination of Apigenin, Catalpol, and Gallic Acid Contents in Plantago Lanceolata L. and Plantago Major L. - Samaneh Rahamouz-Haghighi; Khadijeh Bagheri; Ali Sharafi (Mazandaran University of Medical Sciences, 2023)
Background and Objectives: Plantago is a diverse genus of the Plantaginaceae family. Plantago lanceolata L. (P. lanceolata) and Plantago major L. (P. major) are used commercially worldwide as a traditional treatment for many diseases. A sensitive, simple, and reliable high-performance liquid chromatography (HPLC) method was developed to simultaneously quantify the three active ingredients: apigenin, catalpol, and gallic acid in P. lanceolata and P. major.  Methods: HPLC analysis was carried out using C8 and C18 columns. The mobile phase comprised acetonitrile, orthophosphoric acid, or formic acid (different ratio V/V) with flow rates of 0.4, 0.8, and 1 mL/min. The eluted peaks were detected at 204, 210, 256, and 330 nm. The crude extracts were separated using the liquid-liquid extraction method. Results: HPLC analysis was performed using the C8 column with the mobile phase consisting of acetonitrile-orthophosphoric acid (1:1%) at a 1 mL/min flow rate. The detection of the eluted peaks was observed at 204 nm. Using this protocol, the detection and quantification limits for apigenin, catalpol, and gallic acid were 0.007 and 0.022 μg/mL, 0.04 and 0.14 μg/mL, 0.02 and 0.073 μg/mL, respectively. The calibration curve's correlation coefficient indicated good linearity (r>0.9996, 0.9991, and 0.9978), with average recoveries for the three compounds between 100.02, 95.98, and 108.30%, respectively. Meanwhile, the intra-day and inter-day accuracy averages ranged from 100.07 to 99.95%, respectively. The results showed that using dichloromethane extracts of Plantago species leaves produced the highest yield of apigenin (1.08 and 0.58 μg/mg). At the same time, gallic acid was more abundant in methanolic, butanol, and aqueous extracts of P. lanceolata (3.33 μg/mg) and P. major (3.95, 4.34, and 4.72 μg/mg). The aqueous extract of P. lanceolata leaf and P. major root also showed more catalpol content (9.339 and 2.451 μg/mg).  Conclusion: The developed method indicated reliable results with reproducibility, high accuracy in an analytical run, repeatability, acceptable intermediate precision, reproducibility, and stability of these working solutions. To the best of our knowledge, this study is the first report for the simple, simultaneous quantification of three compounds in Plantago spp. using HPLC.